EFFECT OF LOCATION AND PRODUCT QUALITY ON PURCHASE DECISION OF REXVIN HOUSING BATAM - Deviyanti Deviyanti; Nur Elfi Husda (Jurnal Apresiasi Ekonomi, 2018)
This study aims to determine the effect of location and product quality on the purchase decision at PT Rexvin Propertindo in Batam. This study has a population of 322 people, that is Rexvin Boulevard housing buyers who make purchases in 2014-2016 is 322 people, with a total sample of 178 people with sampling technique is simple random sampling. The data analysis technique used is multiple linear regression analysis using SPSS program. Based on the test results coefficient of determination (R2) of 51% indicates that the location and quality of the product influence the purchase decision. The result of t test shows that t value on location variable is 2,464 and t value on product quality variable is 7,743. Both values t arithmetic greater than the value of t table with a value of 1.974, so that each variable has a positive and significant effect on purchasing decisions. So it can be concluded that the location and quality of products together have a positive and significant impact on purchasing decisions